2019
DOI: 10.1016/j.pmedr.2019.100847
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in knowledge and use of tobacco treatment among smokers in California following healthcare reform

Abstract: The Affordable Care Act (ACA) promised to narrow smoking disparities by expanding access to healthcare and mandating comprehensive coverage for tobacco treatment starting in 2014. We examined whether two years after ACA implementation disparities in receiving clinician advice to quit and smokers' knowledge and use of treatment resources remained. We conducted telephone interviews in 2016 with a stratified random sample of self-reported smokers newly enrolled in the Kaiser Permanente Northern Califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 62 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…Despite this, pervasive racial, ethnic, and socioeconomic disparities exist within the KPGA population. For example, Kaiser Permanente has previously reported racial and socioeconomic disparities with respect to health and well-being [ 38 ], gastric cancer [ 39 ], smoking cessation [ 40 ], and diabetes care [ 41 ], and preliminary evidence suggests that Black members are twice as likely to experience housing instability, indicating that a social gradient exists within this integrated health system. Understanding the underlying mechanisms contributing to racial disparities in COVID-19 in a population with comparatively uniform access to care is the focus of this work, for which the KPGA data infrastructure is well-suited.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, pervasive racial, ethnic, and socioeconomic disparities exist within the KPGA population. For example, Kaiser Permanente has previously reported racial and socioeconomic disparities with respect to health and well-being [ 38 ], gastric cancer [ 39 ], smoking cessation [ 40 ], and diabetes care [ 41 ], and preliminary evidence suggests that Black members are twice as likely to experience housing instability, indicating that a social gradient exists within this integrated health system. Understanding the underlying mechanisms contributing to racial disparities in COVID-19 in a population with comparatively uniform access to care is the focus of this work, for which the KPGA data infrastructure is well-suited.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior literature, one explanation could be the greater awareness and availability of medication treatment versus counseling services for nicotine dependence among the general population of tobacco users 17,18 . For example, one study reported that the majority of smokers were not aware of free counseling services and strategies such patient outreach (e.g., through secure messages) and provider referrals to counseling services could accelerate the use of counseling services among smokers 18 . Another could be that individuals with SUD are more likely to use counseling services for SUD treatment and could prefer medication over counseling for tobacco dependence treatment 32 .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 For example, one study reported that the majority of smokers were not aware of free counseling services and strategies such patient outreach (e.g., through secure messages) and provider referrals to counseling services could accelerate the use of counseling services among smokers. 18 Another could be that individuals with SUD are more likely to use counseling services for SUD treatment and could prefer medication over counseling for tobacco dependence treatment. 32 These results could also reflect broader barriers experienced by Medicaid beneficiaries, including cost, transportation, or absence of local providers, particularly those with SUD, in accessing specialty outpatient mental health care for smoking cessation.…”
Section: The Effect Of Tdt Coverage Expansion On Tdt Use Among Benefi...mentioning
confidence: 99%
See 2 more Smart Citations